Aplicação de processos oxidativos avançados na degradação de propranolol e avaliação de sua toxicidade - Fernandes, Abraão Augusto (2015)
The presence of drug residues has been found in aquatic environments, such as; lakes and rivers and in most cases this type contaminant is found in sewers. This type of pharmaceutical waste may contain an antihypertensive drug class, and one of its main representatives is propranolol (PRO). As a result, this study aimed to apply the advanced oxidation processes (AOPs) as an alternative to removal of this drug in synthetic effluent (SE) and real (RE). This study employed in a photochemical reactor, homogeneous systems of type photolysis, UV/H2O2, Fenton, photo-Fenton, like that TiO2 and ZnO as methods based on heterogeneous catalysis. The parameters for optimization of these methods were evaluated with the assistance of full factorial design. The evaluation of the optimal methods was performed based on the values of the rate of degradation, chemical oxygen demand (COD) and the germination index (GI). The results of better rate degradation (98,3 and 88.6%), reduction of COD (47 and 29.4%) and germination rate (62,2 and 47.2%), were achieved employing a UVC lamp 60W in the method photo-Fenton with a H2O2 concentration of 6 mmol L-1 and a Fe2+ concentration of 0.2 mmol L-1 for the synthetic and real effluent.